Sosyo-Kültürel Açıdan Kelâm ve Hadis İlimlerinde Epistemoloji / The Epistemology in the Sciences of Hadith and Kalam from the Perspective of Socio-Cultural Context - CAGLAYAN, Harun (Journal of History Culture and Art Research, 2016)
The Epistemology in the Sciences of Hadith and Kalam From the Perspective of Socio-Cultural Context The reason is an important source of information in the science of Kalam while the report (khabar) is an important source in the science of Hadith. The nature of these sciences is the main reason of this dichotomy. While Kalam defends and promotes Islamic doctrine, Hadith interests locating the deeds of the prophet (sunnah). Therefore, the sciences of Kalam and Hadith had been perceived as alternative or opponent disciplines to each other through the Muslim history. This study examines determining factors of epistemological approach of Kalam and Hadith by considering socio-cultural dynamics and educational policies of Muslim societies. The article consists of three chapters. The first chapter deals with the Islamic education and institutes. The second chapter handles educational issues related with the sciences of hadith and kalam. The last chapter examines the topic of “khabar (report)” in the sciences of Hadith and Kalam with an epistemological point of view. Öz Kelâm ilminde bilgi kaynağı olarak akla önem verilirken, Hadis ilminde habere önem verilir. Bu yaklaşımın temel nedeni, Kelâm ilminin İslâmî öğretinin savunuculuğunu ve propagandasını yapan aklî bir ilim olmasıdır. Nakli bir ilim olarak Hadis ilmi ise Müslüman toplum yaşamında önemli bir konuma sahip Sünnet’in tespitiyle ilgilenmektedir. Bu farklılıktan dolayı, tarihsel süreç içerisinde Kelâm ve Hadis ilimleri birbirine alternatif veya rakip disiplin gibi algılanmıştır. Bu çalışmada, Müslüman toplumların içinde bulunduğu sosyo-kültürel dinamikler ve eğitim politikaları göz önünde bulundurularak, Kelâm ve Hadis’in epistemolojik yaklaşım tarzını belirleyen faktörlerin neler olduğuna temas edilecektir. Çalışma üç bölümden oluşmaktadır. Birinci bölümde İslam’da eğitim ve eğitim kurumları konularına temas edilmiştir. İkinci bölümde eğitsel açıdan hadis ve kelam ilimleri ile ilgili meseleler ele alınmıştır. Üçüncü bölümde ise epistemolojik açıdan hadis ve kelam ilimlerinde haber konusu incelenmiştir.